Modelling Carbon-energy Metabolism of Cities: A Systems Approach. (June 2016) - Chen, Shaoqing; Chen, Bin
Abstract: Urban metabolism has been widely used in accounting for cities' absorption of energy and materials and elimination of wastes. We aim to introduce a systems approach for modelling carbon metabolism and the influence from energy use activities, thus furthering our understanding of carbon profile in cities. Physical input-output table (PIOT) and material flow analysis (MFA) are used to develop a framework for urban carbon accounting that includes both the carbon flows between sectors and transboundary exchanges between urban economy and natural ecosystems. Based on indicators derived from carbon-energy metabolism modelling, the degree of carbonization is evaluated for cities.